LIKUIDITAS PT. SLJ GLOBAL TBK SEBELUM DAN SELAMA PANDEMI COVID 19 - Elfreda Aplonia Lau; Umi Kulsum (Prodi Ilmu Administrasi Negara, 2022)
This study aims to assess the company's financial performance as measured by the current ratio, quick ratio and cash ratio in two conditions, before the COVID-19 pandemic, in 2017 and 2018 and the condition of the COVID-19 pandemic, in 2019 and 2020. The theory that underlies this research is liquidity using the Current Ratio, Quick Ratio and Cash Ratio analysis tools to the 2017-2020 financial position report data. The results showed that the financial performance of PT. SLJ Tbk in 2017-2020 experienced a decrease in liquidity which indicated the company was categorized as illiquid. This decline in financial performance was due to the company being burdened with current debt which continued to increase and was also affected by the COVID-19 pandemic.